Afro-fabulations the queer drama of Black life - Nyong'o, Tavia (New York University Press, 2019)
"In Afro-Fabulations: The Queer Drama of Black Life, cultural critic and historian Tavia Nyong'o surveys the conditions of contemporary black artistic production in the era of post-blackness. Moving fluidly between the insurgent art of the 1960's and the intersectional activism of the present day, Afro-Fabulations challenges genealogies of blackness that ignore its creative capacity to exceed conditions of traumatic loss, social death, and archival erasure"...
Keywords: American drama -- African American authors -- History and criticism; African Americans in the performing arts; Gays in the performing arts -- United States; Homosexuality in the theater -- United States; LGBT -- Motiv; Ethnische Identität -- Motiv; Drama; Schwarze; USA